2012
DOI: 10.1021/ic202085j
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Isomeric Zinc Metal–Organic Frameworks from a Tetracarboxylate Linker

Abstract: Three porous supramolecular isomers (IZE-1, IZE-2, and IZE-3) with the same framework component [Zn(2)(EBTC)(H(2)O)(2)] (EBTC = 1,1'-ethynebenzene-3,3',5,5'-tetracarboxylate) were successfully constructed by finely tuning the reaction condition. Although both IZE-1 and IZE-2 are constructed from the linear EBTC subunits and one kind of regular [Zn(2)(CO(2))(4)] paddlewheels, their frameworks exhibit two different (3,4)-c net of fof (sqc1575) and sqc1572, respectively, resulting in cavities with different size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Strands of the framework of 1 (Figure b) are interwoven with each other, resulting in the formation of a robust framework. A topology analysis indicates that 1 (Figure c) possesses a 3,4,4-c connected net where the TTPA ligand acts as a three-connecting node and two independent Zn­(II) metal ions act as a four-connecting node for both metal ions. The Schläfli symbol of 1 is represented as (4.8.10) 2 (4.8 2 .10 3 ) 2 (8 2 .10 2 .11 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Strands of the framework of 1 (Figure b) are interwoven with each other, resulting in the formation of a robust framework. A topology analysis indicates that 1 (Figure c) possesses a 3,4,4-c connected net where the TTPA ligand acts as a three-connecting node and two independent Zn­(II) metal ions act as a four-connecting node for both metal ions. The Schläfli symbol of 1 is represented as (4.8.10) 2 (4.8 2 .10 3 ) 2 (8 2 .10 2 .11 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we will seek to expand the chemistry of these linkers to other metal centers. For example, it has also been shown that tetracarboxy linkers when combined with zinc paddlewheels generate novel topologies along with the standard fof topology. , With this in mind we are investigating the combination of novel redox-active polytopic metallacarborane-based linkers with a variety of metal-based nodes in order to generate new families of stimuli-responsive MOFs with new properties and topologies for use in areas such as ion exchange, gas separation, and energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no relevant work has been reported for the application of metal–organic frameworks (MOFs) as precursors to synthesize MoS 2 /TiO 2 nanohybrid catalysts for HER. MOFs are crystalline materials composed of metal nodes and ligand spacers, which have a wide range of applications including gas storage, electrochemical capacitors, lithium ion batteries, molecular separation, catalysis, imaging, sensing, and drug delivery, etc. Recently, MOFs-derived catalysts continue to capture plenty of attention for the following reasons. , First, the regular arrangement of each component in MOF always leads to homogeneous hybrids. Second, the well-aligned and tunable pores in MOF can result in uniform porous materials, which facilitate the mass transport and the products release, allowing high utilization of active species .…”
Section: Introductionmentioning
confidence: 99%